1998
DOI: 10.1606/1044-3894.715
|View full text |Cite
|
Sign up to set email alerts
|

Multigenerational Patterns and Internal Structures in Families in which Grandparents Raise Grandchildren

Abstract: ‘Skipped generation’ families, consisting of grandparents and grandchildren with parents absent from the home, are frequently served in social work agencies. These families have unique multigenerational patterns and family structures that are important for service providers to recognize. This paper uses a multigenerational systems perspective to highlight the diversity among grandparent-headed households. Twenty families who were previously part of a larger study of stress, well-being, and life satisfaction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The most compelling contextual factor stressed in the literature was financial strain, emerging as a major issue faced by grandmothers raising grandchildren. Several studies found grandmother-onlyheaded households to be the poorest and, in fact, 50% to 60% of these families were found to be below the poverty level (Fuller-Thomson & Minkler, 2000;Fuller-Thomson et al, 1997;Goldberg-Glen, Sands, Cole, & Cristofalo, 1998). Roe and Minkler (1995) did not find any grandmothers who benefited economically after taking responsibility for grandchildren, and many had experienced a substantial financial decline.…”
Section: Povertymentioning
confidence: 99%
See 2 more Smart Citations
“…The most compelling contextual factor stressed in the literature was financial strain, emerging as a major issue faced by grandmothers raising grandchildren. Several studies found grandmother-onlyheaded households to be the poorest and, in fact, 50% to 60% of these families were found to be below the poverty level (Fuller-Thomson & Minkler, 2000;Fuller-Thomson et al, 1997;Goldberg-Glen, Sands, Cole, & Cristofalo, 1998). Roe and Minkler (1995) did not find any grandmothers who benefited economically after taking responsibility for grandchildren, and many had experienced a substantial financial decline.…”
Section: Povertymentioning
confidence: 99%
“…In summary, the surrogate grandparent is typically female (Sands & Goldberg-Glen, 2000), African American (Casper & Bryson, 1998;Fuller-Thomson et al, 1997), unmarried (Casper & Bryson, 1998;Fuller-Thomson & Minkler, 2000;Sands & Goldberg-Glen, 2000), unemployed (Casper & Bryson, 1998), living at or below the poverty level (Casper & Bryson, 1998;Fuller-Thomson & Minkler, 2000;Fuller-Thomson et al, 1997;Goldberg-Glen et al, 1998;Sands & Goldberg-Glen, 2000), and undereducated (Casper & Bryson, 1998;Goldberg-Glen et al, 1998). Additionally, they fear being unable to raise their grandchildren to adulthood.…”
Section: Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…It offers a graphic representation of the intricate relationships in the developmental stages of families influencing family structure and change (McGoldrick & Gerson, 1985). The genogram has been used as a research tool for data collection by various scholars across disciplines to explore multigenerational patterns and internal family structures in grandparentheaded households (Goldberg-Glen, Sands, Cole, & Cristofalo, 1998); violence against women in Zimbabwe and Latin America (Watts & Shrader, 1998); and family functioning and structure (DeMaria, Weeks, & Hof, 1999). The genogram was used to visually capture grandparenting household structure and detailed information about its family members.…”
Section: Data Collectionmentioning
confidence: 99%
“…This includes reports of stress (Goldberg-Glen, Sands, Cole, & Cristofalo, 1998; Haglund, 2000; Kelley, 1993). Other studies document depression among orphan carers (Burton, 1992; Fuller-Thomson & Minkler, 2000; Goldberg-Glen, et al, 1998; Jendrek, 1993; Minkler & Roe, 1993; Roe, Minkler, Thompson, & Saunders, 1996; Szinovacz, DeViney, & Atkinson, 1999). …”
Section: Introductionmentioning
confidence: 99%